Serum vitamin D status in children with epilepsy on antiepileptic drugs and its relation to the frequency of breakthrough seizures - Bezboruah, Gayatri; Kalita, Shabnam (International Journal of Contemporary Pediatrics, 2023)
Background: Epilepsy is the most common neurological disorder in children requiring long term drug therapy which are associated with vitamin D deficiency. Antiepileptic actions of vitamin D deficiency have been extensively studied in animal models but human data, particularly in children is lacking. Objectives were to study the levels of serum vitamin D in children with epilepsy on antiepileptic drugs and to study the correlation between levels of vitamin D and frequency of breakthrough seizures. Methods: hospital-based cross-sectional study. Participants: A total of 94 children with epilepsy were included in the study. Intervention: The patients were on a minimum of 6 months of antiepileptic drug therapy. Anthropometric measurements were taken and blood samples were analysed for vitamin D, serum calcium, phosphate, complete blood counts and renal profile. Results: The present study showed a statistically significant relationship between serum vitamin D deficiency and antiepileptic drugs (p value <0.001), the number of AEDs with patients on polytherapy ≥2 AEDs having lower vitamin D levels (p value <0.001) and the duration of antiepileptic drugs (p value of 0.016). Linear regression analysis also showed a statistically significant relationship between serum vitamin D deficiency and seizure frequency (p value of <0.001, 95% confidence interval: -3.465, -2.275). Conclusions: Case studies and epidemiological data also support the evidence of connection between levels of serum vitamin D and epilepsy and the use of vitamin D3 as a potential therapy for human epilepsy. This study is conducted with an aim to highlight the role of vitamin D in children with epilepsy in seizure control.